Role of colonizers and value of routine surveillance culture of endotracheal aspirate of patients in the diagnosis of ventilator associated pneumonia - Siddique, Sana; Haider, Fareya; Ahmad, Sharique; Iqbal, Khalid; Singh, Mastan (Asian Journal of Medical Sciences, 2020)
Background: Ventilator associated pneumonia (VAP) is considered to be second most common nosocomial infection patients requiring critical care. Aims and Objective: The present study was conducted to study the role of colonizers and importance of surveillance cultures of endotracheal aspirate (ETA) in the diagnosis of ventilator associated pneumonia in a tertiary care hospital in Lucknow. Materials and Methods: An observational longitudinal study was conducted over a period of 2 years, on a total of 210 critically ill patients on mechanical ventilation for >48hrs, to identify the common isolates from ETA culture. Follow up of such patients was done to know the role of these isolates in causation of Ventilator Associated Pneumonia (VAP). Patients fulfilling both clinical Pulmonary infection score (CPIS>6) and microbiological criteria were diagnosed as VAP. Those microorganisms with a colony count of less<105 cfu/ml in both the patients with VAP and those without VAP were considered as colonizers. Results: Klebseilla pneumonia (46.2%), Pseudomonas aeruginosa (16.2%) and E.coli (13.8%) were found be the commonest colonisers followed by Acinetobacterbaumanii (8.6%), Citrobacterkoseri (3.8%), Coagulase Negative Staphylococci (2.9%), Staphylococcus aureus (2.4%) and Proteus vulgaris (1%). Of the total patients 28 developed VAP out of which 21 had late onset VAP and 7 had early onset VAP. Among the VAP positive patients the causative organism was Klebsiella pneumonia (53.6%) for majority of cases followed by Pseudomonas aeruginosa (21.4%) and Acinetobacter baumanii (17.9%). Conclusion: Prolonged duration of mechanical ventilation increased the chances of colonization by MDR microorganisms leading to nosocomial or Hospital acquired infections (HAI) such as VAP which in turn lead to increased rate of morbidity and mortality. VAP considered to be a leading cause of HAI, routine quantitative surveillance culture of ETA(endotracheal aspirate) will allow prospectively to determine prevalence and progression of colonization in lower respiratory tract, so that strict and prompt preventive measures can be taken rather than cure.